Bagaimana Petani dalam Pengelolaan Risiko? Persepsi dan Perilaku Petani Tebu di Jawa Timur - Intan Mega Maharani; Nuhfil Hanani; syafrial syafrial (JSEP (Journal of Social and Agricultural Economics), 2023)
One of the challenges of increasing sugarcane productivity is that unpredictable external factors expose farmers to a variety of risk production, necessitating farmers to adapt to these changes. This study intends to examine farmers' perceptions and behavior toward risk as an alternative to a new strategy for increasing sugarcane productivity through 237 samples of sugarcane farmers in East Java. The Just and Pope model was utilized to analyze risk preferences and the probit regression model was utilized to identify the socioeconomic elements influencing this behavior. According to the perception analysis, productivity is significantly influenced by climate, pests and diseases, labor, and land area. However, farmers typically only make passive adjustments, which is consistent with the analysis that they are risk- averse. This attitude is significantly influenced by age, whereas factors like farming experience, size of the family, off-farm, and education have insignificant impacts. To anticipate the unpredictable external changes and raise the farmer's quality, it is suggested to increase the frequency of training and the use of technology. This will encourage farmers to take more chances and be more open to using new technologies.